2021
DOI: 10.1111/are.15178
|View full text |Cite
|
Sign up to set email alerts
|

Dysbiosis of the shrimp ( Penaeus monodon ) gut microbiome with AHPND outbreaks revealed by 16S rRNA metagenomics analysis

Abstract: Acute hepatopancreatic necrosis disease (AHPND) or early mortality syndrome (EMS) is a severe hepatopancreatic disease of shrimp, which is mainly caused by Vibrio parahaemolyticus (Vp;Han, Tang, Pantoja, et al., 2015). AHPND was first diagnosed in China in 2009.Since then, this emerging disease has spread globally and caused substantial economic losses throughout its history. It affects both Penaeus monodon and Litopenaeus vannamei (Lai et al., 2015). Vibrio parahaemolyticus is a conditional pathogen of gram-n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 78 publications
(88 reference statements)
1
10
0
Order By: Relevance
“…The genera Psychrobacter, Pseudomonas, Flavobacterium, Chryseobacterium, Enterobacter, Ralstonia and Brevibacterium were significantly different in each locations and in each part of the healthy and diseased samples. LDA analysis could differentiate the microbiome clusters and their effects on healthy and diseased fishes, and microbiome clusters were also differentiated in healthy and diseased Yunlong Grouper and shrimp ( Ma et al, 2019 ; Hossain et al, 2021 ). LDA analysis detected 1 phylum, 3 classes, 6 orders, 4 families and 4 genera; among them, in healthy fishes, Runella and Rhodobacter had the highest scores, while in infected fishes, Flavobacterium columnare and Firmicutes showed the highest scores, similar to the findings of Zhang et al (2018) .…”
Section: Discussionmentioning
confidence: 99%
“…The genera Psychrobacter, Pseudomonas, Flavobacterium, Chryseobacterium, Enterobacter, Ralstonia and Brevibacterium were significantly different in each locations and in each part of the healthy and diseased samples. LDA analysis could differentiate the microbiome clusters and their effects on healthy and diseased fishes, and microbiome clusters were also differentiated in healthy and diseased Yunlong Grouper and shrimp ( Ma et al, 2019 ; Hossain et al, 2021 ). LDA analysis detected 1 phylum, 3 classes, 6 orders, 4 families and 4 genera; among them, in healthy fishes, Runella and Rhodobacter had the highest scores, while in infected fishes, Flavobacterium columnare and Firmicutes showed the highest scores, similar to the findings of Zhang et al (2018) .…”
Section: Discussionmentioning
confidence: 99%
“…The beta diversity parameters, including Bray‐Curtis dissimilarity, Euclidean distance, Jaccard coefficient, and Manhattan distance were also calculated and plotted as PCOA diagrams using Usearch software (Edgar, 2010 ) and R software (Team RC, 2013 ). The raw data sequences (healthy and infected samples) of previous studies (Foysal et al., 2021 ; Hossain et al., 2021 ) were retrieved from NCBI database (BioProject ID: PRJNA662111; PRJNA662500) and used in the beta diversity analysis for cross comparison purpose. A Venn diagram was plotted using Mothur software (Schloss et al., 2009 ) and R software (Team RC, 2013 ).…”
Section: Methodsmentioning
confidence: 99%
“…studies (Foysal et al, 2021;Hossain et al, 2021) were retrieved from NCBI database (BioProject ID: PRJNA662111; PRJNA662500) and used in the beta diversity analysis for cross comparison purpose. A Venn diagram was plotted using Mothur software (Schloss et al, 2009) and R software (Team RC, 2013).…”
Section: F I G U R E 1 Overall Pathogenic and Toxin Flow Of Ahpnd Inf...mentioning
confidence: 99%
“…In particular, shrimp diseases lead to significant economic losses. The dysbiosis of the intestine can contribute to several shrimp diseases, such as acute hepatopancreatic necrosis disease (AHPND) and white feces syndrome (WFS) ( Hossain, Dai & Qiu, 2021 ; Huang et al, 2020a ). Recently, Wu et al (2021) revealed that dysbiosis in the hepatopancreatic microbiota of the crayfish ( Procambarus clarkii ) is associated with disease outbreaks.…”
Section: Introductionmentioning
confidence: 99%